Temporal Polyethism and Life Expectancy of Workers in the Eusocial Wasp Polistes canadensis canadensis Linnaeus (Hymenoptera: Vespidae) - Viviana de Oliveira Torres; Edilberto Gianotti; Willian Fernando Antonialli-Jr. (Sociobiology)
The division of tasks among nestmates is one of the most important traits of the social Hymenoptera, and is responsible for their evolutionary success. This division of labor, which occurs among workers throughout their lives, is called temporal polyethism. This study investigated how temporal polyethism occurs, and its effects on the life expectancy of the eusocial wasp Polistes canadensis canadensis Linnaeus. To evaluate the different activities and determine longevity, newly emerged females were individually marked with colored dots on the mesosome. During their lives, workers perform 22 behavioral acts, and the Nonmetric Multidimensional Scaling analysis revealed a variation in the pattern of behaviors performed until the fifth week of life, i.e., close to their mean longevity. The mean life expectancy was 37.06 ± 29.07 days, with a mortality rate of 24.14% in the first week, coinciding with the onset of foraging activity. In other, less-derived species this began early in the life of the workers. The high entropy value (H = 0.750) reflects the high mortality rate in the first weeks of life.